Pengaruh Strategi Green Marketing Terhadap Kinerja Keuangan Dan Non-Keuangan Perusahaan - Yuni Adinda Putri; Rifani Akbar Sulbahri; Gumulya Sonny Marcel Kusuma (Akuntansi dan Manajemen, 2023)
This study aims to present a reflection of the literature on green marketing strategies and analyze seven factors that will affect company performance. This research refers to the literature review method. As green marketing strategies become increasingly important for companies following the triple bottom line performance evaluation, this research seeks to better understand the role of the "green marketing mix" as a marketing strategy. This model links the relationship between green marketing strategies, including green product, green price, green promotion, green distribution, green people, green process, and green physical evidence, with company performance, including financial and non-financial performance. The results of the study show that the green marketing strategy has a positive effect on the company's financial and non-financial performance. From the discussion above, it can be concluded that this research extensively reviews the literature in the field of green marketing strategy and highlights that companies that adopt green marketing strategies (green product, green price, green distribution, green promotion, green people, green process, and green physical evidence) are expected to generate more profits than firms that do not adopt the strategy.